The nerve of facial expression, impact of its anatomical variations on iatrogenic surgical injury and a novel MRI diffusion weighted imaging technique to image its intra-parotid course - EL KININY, WALID HOSAM (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2018)
This doctorate in clinical medicine set out to assess how variations in facial nerve anatomy to the intra-parotid venous system could impact on surgical access to the parotid gland or the mandible, and explored methods to help reduce the risk of iatrogenic facial nerve injury. The vast majority of surgical descriptions in parotid or extra-oral mandibular surgery rely on the normally described relationship of the facial nerve to predefined surgical landmarks and intra-parotid venous structures. Published reports on the incidence of the iatrogenic facial nerve injury vary widely according to speciality and institutions. What is known is that multiple specialities require the skills and knowledge to operate safely in or around the parotid gland where the extra-cranial facial nerve is put at risk. A recent systematic review of maxillofacial extra-oral access to the mandibular condyle, involving eight-multicentre studies showed incidence of iatrogenic facial nerve injury of up to 11%, with some studies suggesting incidence rates of up to 42% with particular approaches. The impact of anatomical variation on surgical technique was not considered in any of the reports and neither was the potential for preoperative imaging of the facial nerve. Imaging of the extra-cranial facial nerve has historically been extremely difficult despite the wide availability of imaging methods available today. Diffusion weighted magnetic resonance imaging of intracranial white-matter tracts has shown great success in recent years. The application of this method of imaging of extra - central nervous system neural tracts is now being explored. This doctorate aims to assess the feasibility of reproducing the facial nerve white-matter tract as it courses through the parotid gland. The first arm of this doctorate research project involved detailed dissections of the facial nerve in a cohort of cadaveric subjects donated to the anatomy department of Trinity College Dublin. Facial nerve variation to predefined surgical landmarks was analysed with respect to potential impact on surgical technique. With respect to the 'safe zone' utilised in making a pre-auricular incision, a 'safe zone' of 6mm was identified between the most anterior point of the external auditory meatus and the most posterior branch of the temporal nerve. As such, 6mm is the distance advocated by this study, marking a reduction in the distance previously advocated and currently widely practised whereby it would be safe to make a pre-auricular incision to access the parotid gland or the temporomandibular joint while avoiding inadvertent damage to the temporal branch of the facial nerve. Additionally, as part of the first arm of this project, intra-parotid venous structures and their relations to the facial nerve were analysed with respect to potential impact on surgical technique. A novel, previously unreported variation of the facial nerve and the superficial temporal vein was discovered, and subsequently published. The second arm of this doctorate research project involved cadaveric diffusion weighted magnetic resonance imaging of the head and neck, followed by detailed dissections of the facial nerve. Extra-cranial facial nerve tracts were identified and anatomically validated. The imaging parameters used were successfully applied to live subjects with disease free parotid glands, thereby proving the feasibility of imaging the extra-cranial facial nerve tract. The profound clinical implications of this are elaborated, especially in the context of helping avoid iatrogenic facial nerve injury, where prevention far outweighs the limited and arduous possibility of nerve repair and cure.
APPROVED
Keywords: Parotidectomy; Facial nerve; Temporomandibular joint; Diffusion weighted magnetic resonance imaging; Tractography; Tragal pointer; Safe zone pre-auricular approach; Retromandibular vein; Superficial temporal vein; Facial palsy; Facial nerve imaging; Extra-cranial facial nerve; Parotid staging